2017
DOI: 10.1086/692662
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Observations of Elementary Mathematics Instruction and Student Achievement: Exploring Variability across Districts

Abstract: Much debate surrounding teacher quality has focused on students' standardized test scores, but recent federal and state initiatives have emphasized the use of multiple measures to evaluate teacher quality, including classroom observations. In this study, we explore differences across school districts in the relationship between student achievement outcomes and the observed quality of teachers' instruction. Using data from 298 elementary mathematics teachers in five urban US districts, we examine relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…First, districts supplied student scores on state mathematics tests for the years of the study and for up to 2 years prior; many schools and teachers experienced these as high-stakes assessments due to No Child Left Behind regulations. These state tests ranged in content, from two that primarily focused on basic skills and problem-solving to one—used in two study districts—that required more complex thinking and communication about mathematics (Lynch, Chin & Blazer, 2017). Second, sampled students completed a project-developed mathematics test in the spring semester of each school year.…”
Section: Methodsmentioning
confidence: 99%
“…First, districts supplied student scores on state mathematics tests for the years of the study and for up to 2 years prior; many schools and teachers experienced these as high-stakes assessments due to No Child Left Behind regulations. These state tests ranged in content, from two that primarily focused on basic skills and problem-solving to one—used in two study districts—that required more complex thinking and communication about mathematics (Lynch, Chin & Blazer, 2017). Second, sampled students completed a project-developed mathematics test in the spring semester of each school year.…”
Section: Methodsmentioning
confidence: 99%
“…Districts 1 and 2 come from the same state and utilize the same set of curriculum materials, Investigations , that was designed to support the mathematics reforms of the 1990s–2000s. Using an adapted version of the Surveys of Enacted Curriculum framework (Porter, 2002) to code state test items, Lynch, Chin, and Blazar (2015) found that the state assessment administered in both districts contained moderately cognitively challenging items and a higher level of academic difficulty than the other two state tests in the study. Interviews with district math coordinators suggest that District 1 had a decade-long and intensive effort to provide principals, teachers, and teacher leaders with professional development and coaching around ambitious instruction.…”
Section: Methodsmentioning
confidence: 99%
“…It likely also is similar to new mathematics assessments administered under the Common Core (National Governors Association Center for Best Practices, 2010). Lynch, Chin, and Blazar (2015) coded items from this assessment for format and cognitive demand using the Surveys of Enacted Curriculum framework (Porter, 2002). They found that the assessment often asked students to solve non-routine problems, including looking for patterns and explaining their reasoning.…”
Section: Student Demographic and Test-score Datamentioning
confidence: 99%